Pembelajaran Berdiferensiasi Berbasis Joyful Learning untuk Meningkatkan Pemahaman Numerasi Siswa - Setyaningsih, Niken Dwi; Dayu, Dian Permatasari Kusuma; Nafisah, Durrotun (PAKAR Pendidikan, 2024)
Differentiated learning allows students to learn more effectively according to their learning styles and interests. The purpose of this study is to describe the application of differentiated learning based on learning pleasure to student's numerical comprehension. The participants in this study were 25 junior high school students in Indonesia (12 female students and 13 male students) aged 9 to 10 years old. Observation results in cycle I showed that student activity reached 70%, and in cycle II, student activity increased to 80%. Data analysis techniques using classroom action research. Techniques carried out in the data collection process, namely observation, interviews and tests. The research was conducted in two cycles, with one meeting per cycle. The results showed that learning in cycle I and cycle II at each stage of learning could be carried out well. The results of this study indicate that learning activities using differentiated learning based on learning pleasure can improve students' numerical understanding. So, based on the results and discussion, differentiated learning based on joyful learning affects students' numerical understanding.